A new species of Cucullanus (Nematoda: Cucullanidae) parasite of Genypterus blacodes and G. brasiliensis (Pisces: Ophidiidae) in the South West Atlantic - Sardella, Norma Haydée (1997)
Cucullanus genypteri sp. n, a parasite of Genypterus blacodes Schneider, 1801 and G. brasiliensis Reagan, 1903 (Pisces: Ophidiidae) from different zones of the South West Atlantic Ocean is described and illustrated. The new species is distinguished from other south american members in the genus Cucullanus Mueller, 1777 by the distribution pattern of caudal papillae and by the body measurements, particularly spicule length. C. genypteri represents the first description of a marine species of this genus from Argentina. Variations of parasitism in relation to host size, sex and geographic distribution are also discussed.